VASYL STEFANYK – IVAN CANCAR: TYPOLOGY OF ARTISTIC THINKING - Maftyn, Natalia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The importance of the article lies in the need to study Ukrainian-Slovenian relations, in particular at the level of two prominent representatives of modernism, Ukrainian and Slovenian ones, – Vasyl Stefanyk and Ivan Cankar. There exists only a small amount of works concerning comparative studios of the Ukrainian and Slovenian literatures. Moreover, there are no scientific works devoted to the personalities of V. Stefanyk and I. Cankar, whose fates and artistic views have much in common, although there is no evidence of possible direct contacts between them. The study of the chosen problem makes it possible to expand the Slavic context of the Ukrainian modern literature and to look at the era through the prism of the writers’ fates and works, as the idea of the "evolutionary history of literature" gives way to the "study of the history of writers". Both writers were citizens of the Habsburg Empire and lived in the same period. Both Ukrainian and Slovenian writers were influenced by European modernism, and their artistic pathes of developing individual style strategies went through iconic cities – the centers of the European modernism culture (for V. Stefanyk it was Krakow, for I. Cankar – Vienna). However, both writers manifest their national core as their creative basis. Both writers reacted to the same social challenges of their epoch (the topics of emigration, and war, commoners’ lives, difficult childhood). Their works revolve around the dominant of the tragic. Additionally, there is a strong feeling of marginality inherent in their works: being citizens of a large empire, neither V. Stefanyk nor I. Cankar belonged to the representatives of the titular nation. This manifested in their understanding of commitment to the "service to the community" which was quite clearly declared in the work of the two writers. The typology of artistic thinking of the Slovenian and Ukrainian authors in the article is traced at the thematic, genre, and stylistic levels. The research encompasses the analysis of the ideological and artistic, genre and style features of the lyrical sketches "The Road" by V. Stefanyk and "My Field" by I. Cankar, the story "Batrak Jernej and his right", the short stories "Holy Communion", "Old and children" by I. Cankar and the shorts stories by V. Stefanyk "Arsonist", "Thread", "Child' s Adventure", which reveals the typology of artistic thinking of the two authors at the level of personal and biographical motivation, and at the same time the research work focuses on the differences that can be explained by the specifics of both the mental organization of the writers and the existence of "national archetypes" deeply rooted in them.